Communication Strategies Framework In Wildlife Trafficking Using Social Media: A Netnography Study - Santhanasamy, Esther (2024)
In Malaysia, online wildlife trade is prevalent whereby social media sites such as Facebook (FB) and Instagram (IG) are used to advertise endangered animals. Even though online wildlife trade is a threat, not much studies have been conducted in the field of communication in Malaysia. Thus, this present study aims to examine the communication process between the sellers and buyers of wildlife on social media sites (FB and IG).